Analisis Data Variabel Iklim Mikro Dengan Menggunakan Statistik Deskriptif (Studi Kasus Pemukiman Kelurahan Kampung Lapai Kecamatan Naggalo Padang) - Nelvidawati; Surtia Bachtiar, Vera (Dampak, 2025)
Urban areas are vulnerable to the urban heat island (UHI) phenomenon. The analysis of microclimate parameters is one of the important steps to understanding environmental dynamics on a local scale. This study aims to analyze microclimate parameters such as temperature, humidity, wind speed, heat intensity of sunlight, and rain intensity measured for 5 (five) consecutive days. The analysis carried out was a descriptive statistical analysis. The analysis of the concentration of variable temperature and high sunlight intensity data resulted in urban heat islands in residential areas because the roofs used were zinc. Zinc could absorb heat, increasing the temperature during the day if it is not raining. The sun's intensity began to peak from 09.00 WIB to 12.00 WIB. The occurrence of rain can reduce the temperature and intensity of sunlight and increase humidity so that there are no urban heat islands in residential areas that can affect thermal comfort. Other microclimate variables, such as wind speed and rainfall, do not have an impact because wind speed is relatively slow and rainfall is moderate. The analysis of the data spread seen from the standard deviation shows that the data tends to be homogeneous. Large data ranges occurred at the variables of temperature, humidity, and sunlight intensity, showing significant variations. Wind speed and precipitation have a small range, indicating the weather's stability at the observation site at the time of measurement. The average population estimated to have a confidence level of 95% is almost the same as the average sample, indicating that the data obtained is close to the actual condition.